Neurostimulation Techniques for the Treatment of Epilepsy - Rosculet, Nicholas J.; Stafstrom, Carl E. (Journal of Pediatric Epilepsy, 2017)
For the one-third of patients with epilepsy whose seizures are refractory to medications and who are not surgical or dietary therapy candidates, alternative therapies such as neurostimulation provide a promising alternative. Neurostimulation techniques include vagus nerve stimulation, deep brain stimulation (particularly stimulation of the anterior thalamus), and responsive neurostimulation. Accumulating data support neurostimulation techniques as a safe and effective option for seizure reduction and improved quality of life for drug-refractory patients.
Keywords: vagus nerve stimulation; deep brain stimulation; responsive neurostimulation